Impact of body mass index on treatment outcome of neoadjuvant chemoradiotherapy in locally advanced rectal cancer. Issue 10 (October 2017) - Sun, Y.; Xu, Z.; Lin, H.; Lu, X.; Huang, Y.; Huang, S.; Wang, X.; Chi, P.
Abstract: Aim: To determine the effect of obesity, measured by body mass index (BMI), on tumor response and surgical outcome in patients with locally advanced rectal cancer (LARC) undergoing neoadjuvant chemoradiotherapy (nCRT) and radical surgery. Method: LARC patients undergoing nCRT and radical surgery from 2008 to 2014 were included and divided into three groups: non-obese (BMI < 25.0 kg/m 2 ), obese I (BMI 25.0–29.9 kg/m 2 ), and obese II (BMI ≥ 30.0 kg/m 2 ). Tumor response, surgical and oncological outcome were compared between groups. Multivariate analyses were performed to identify risk factors for local recurrence. Results: A total of 522 LARC patients were analyzed (407 non-obese, 93 obese I, 22 obese II). Post-operative complications did not differ between groups. Increased BMI was associated with poorer T downstaging and Rectal Cancer Regression Grade (P = 0.116, P = 0.036). With a mean follow-up of 57 months, the 5-year overall survival and distant metastasis rates did not differ between groups (P = 0.861, P = 0.116). The 5-year local recurrence rate in obese II patients was 14.6%, higher than that in non-obese and obese I groups (P = 0.015). Cox regression analysis demonstrated that BMI ≥30 kg/m 2 (HR = 6.187, P = 0.010) was significantly associated with increased risk for local recurrence. Conclusion: Obesity was associated with poorer T downstaging and Rectal Cancer Regression Grade, and thus poor local control in LARC following nCRT in Asian patients. More effective treatment strategies to improve treatment outcome for obese patients with LARC are warranted.